2017
DOI: 10.1111/ejn.13672
|View full text |Cite
|
Sign up to set email alerts
|

Strong long‐range temporal correlations of beta/gamma oscillations are associated with poor sustained visual attention performance

Abstract: Neuronal oscillations exhibit complex amplitude fluctuations with autocorrelations that persist over thousands of oscillatory cycles. Such long-range temporal correlations (LRTC) are thought to reflect neuronal systems poised near a critical state, which would render them capable of quick reorganization and responsive to changing processing demands. When we concentrate, however, the influence of internal and external sources of distraction is better reduced, suggesting that neuronal systems involved with susta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
71
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 51 publications
(80 citation statements)
references
References 59 publications
4
71
1
Order By: Relevance
“…As a consequence, frequent switching between focusing on the sensations of breathing and mind-wandering may have occurred. This, in turn, may have resulted in more complex variability in oscillatory brain activity and a higher DFA exponent in the control cohort, which is analogous to recent findings of reduced LRTC when subjects successfully attend to a sustained visual attention task (Irrmischer et al, 2017).…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…As a consequence, frequent switching between focusing on the sensations of breathing and mind-wandering may have occurred. This, in turn, may have resulted in more complex variability in oscillatory brain activity and a higher DFA exponent in the control cohort, which is analogous to recent findings of reduced LRTC when subjects successfully attend to a sustained visual attention task (Irrmischer et al, 2017).…”
Section: Discussionsupporting
confidence: 76%
“…Critical‐state dynamics in the brain have been related to optimal information processing (Shew & Plenz, ) and the degree to which the brain remains capable of quick reorganization (Deco, Jirsa, & Mcintosh, ; Singer, ; Tognoli & Kelso, ) and, thus, is responsive to natural environments (Beggs & Plenz, ). It has been found that the temporal structure of these oscillations are influenced by performing a task (Irrmischer, Sangiuliano Intra, Mansvelder, Poil, & Linkenkaer‐Hansen, ; Palva & Palva, , Palva, et al, ) and that these oscillations are associated with trial‐by‐trial variability in performance (He & Zempel, ; Linkenkaer‐Hansen, Nikulin, Palva, Kaila, & Ilmoniemi, ), and dynamics of finger‐tapping errors (Smit, Linkenkaer‐Hansen, & de Geus, ). So far it has not been shown if these dynamics in neuronal oscillations are also influenced in the absence of an overt task, by the mere intention to switch our focus from a thinking resting state to a meditative focused attention state.…”
Section: Introductionmentioning
confidence: 99%
“…Time windows corresponded to equally spaced points on a logarithmic scale of data lengths corresponding to 5-14 s for the theta band, 2-14 s for the alpha band, and 1-14 s for beta (50% window overlap). These window sizes were selected to exclude temporal autocorrelations introduced by the band-pass filters (Irrmischer et al, 2018b). The DFA exponent is the slope of the line fitted through the fluctuation amplitudes against window lengths plotted on a logarithmic scale .…”
Section: Detrended Fluctuation Analysismentioning
confidence: 99%
“…Ongoing brain activity appears to function close to an unstable equilibrium point (Deco and Jirsa, 2012). This critical state, where the system is on the boundary between order and disorder (Beggs and Timme, 2012), has been linked to efficient information processing and optimal behavioural performance (Irrmischer et al, 2018b;Palva et al, 2013;Palva and Palva, 2018). A system in a critical state is characterised by scale-free activity distributions and long-range temporal correlations (LRTC; Plenz and Thiagarajan, 2007), which can be measured with techniques such as detrended fluctuation analysis (Peng et al, 1995).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation